Sentiment Analysis Tools, Process, Methodologies: A Survey - Dhaval Bhoi, Dr. Amit Thakkar (International Journal of Advanced Science and Technology, 2020)
The World is now connected planetary, due to the progression of technologies and devices, consequently becoming a global village. Due to numerous practical applications sentiment analysis issue touches the attention of researchers interested in the area of NLP (Natural Language Processing. Digital resources like online information feedback, reviews are essentially important sources to find stakeholders’ input and feedback. Tons of data generated from micro-blogging sites are analyzed qualitatively and quantitatively. Sentiment Analysis is found a quite challenging task especially due to tiny text, spellings mistake, words of shorten form, which leads to sparsity and high dimensionality. Sentiment analysis is becoming favorite among researchers community in recent years and can be applied in varied application areas like healthcare informatics, hospital, sports, financial sector, box office prediction, politics, tourism, and consumer activities and behavior. Towards this end, here in this paper, we have carefully surveyed the sentiment analysis process, sentiment classification algorithms, various datasets, tools/software for performing sentiment analysis and elaborated performance evaluation measurement criteria. Keywords: Sentiment Analysis, Sentiment Tools, Machine Learning Algorithms, Sentiment Classification.